(untitled) - Handbook of energy efficiency and renewable energy; Kreith, Frank (Boca Raton, 2016)
Revised edition of: Handbook of energy efficiency and renewable energy / edited by Frank Kreith, D. Yogi Goswami. 2007; Includes bibliographical references and index
Keywords: Energy conservation -- Handbooks, manuals, etc.; Renewable energy sources -- Handbooks, manuals, etc.; Bảo tồn năng lượng -- Sổ tay; Nguồn năng lượng tái tạo -- Sổ tay